Grazing exclusion unleashes competitive plant responses in Iberian Atlantic mountain grasslands. Issue 1 (23rd November 2016) - Odriozola, Iñaki; García‐Baquero, Gonzalo; Fortin, Marie‐Josée; Laskurain, Nere Amaia; Aldezabal, Arantza
Abstract: Questions: Does the absence of equalizing mechanisms after cessation of grazing unleash strong above‐ground competitors to create large patches in the community? Do these competitive intraspecific aggregations displace and exclude other species, thereby reducing species diversity? Location: Atlantic grasslands, Aralar Natural Park, Basque Country, Northern Iberian Peninsula. Methods: Large herbivores were experimentally excluded from three sites (50 m × 50 m exclusion fences) during 9 yr in a productive semi‐natural grassland system with a long history of grazing, using adjacent grazed plots as experimental controls. Sampling was carried out by systematically placing 100 quadrats (0.5 m × 0.5 m) in each of the six plots. Floristic composition and abundance, as well as eight hydrological and chemical soil properties, were measured in each quadrat. The spatial structures created by competitive species were analysed using RDA in conjunction with Moran's eigenvector maps, and soil variables were simultaneously included in the analyses, thus disentangling the structures likely created by niche effects. Competitive exclusion was further determined using linear regressions between species richness and abundance of competitive species. Results: Grazing exclusion unleashed competitive species such as Festuca microphylla and Agrostis capillaris, which became dominant in the exclusion plots and created large spatial patches. Furthermore, a negative linear relationship, consistent across exclusion plots, was observed between species richness and abundance of competitive species, indicating that strong above‐ground competitors outcompeted other species when herbivores were excluded. However, the outcome of grazing exclusion across sites depended to some extent on local environmental conditions (niche effects). Conclusions: This work confirms that the powerful equalizing mechanism of disturbance by herbivores is crucial for species co‐existence in productive grasslands. However, important differences observed in environmental effects across sites suggest that, even in highly productive grasslands, plant traits and local environmental characteristics (niche effects) do matter for species co‐existence. Abstract : We used a livestock exclusion experiment in the northern Iberian Peninsula to disentangle the effect of competitive interactions and environmental forcing on grassland spatial patterns. Our results show not only that the equalizing mechanism of grazing is critical for species co‐existence, but also that soil properties modulate species competitive interactions. Niche effects matter for species co‐existence, even in productive grasslands.